A WORKSHOP ON UTILIZING NEARPOD: SOLUTION FOR HYBRID HOME-BASED LEARNING IN THE NEW NORMAL - Paulina Erawati Paramita; Dudy Effendy (Nindikayla Institute, 2023)
This article provides an overview of the workshop on